1992
DOI: 10.2527/1992.70113627x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics in immature animals: a review

Abstract: Differences in drug pharmacokinetics between newborn and adult mammals are reviewed. The pharmacokinetic alterations during the maturation process are related to changes in the pattern of absorption, distribution, metabolism, and renal excretion. The most pronounced feature in neonates vs adults is the prolonged elimination half-life of drugs. The main factors causing delayed elimination are under-developed renal clearance and immature metabolism of drugs. Special attention has to be paid to central nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…As the animal grows up, the ability to metabolize xenobiotics becomes greater, reaching the adult level in a variable period depending on the enzyme and the species involved [18,22], However, this rule has ex ceptions. Some enzymes have been reported to have an ontogenic development similar to that described in the present report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the animal grows up, the ability to metabolize xenobiotics becomes greater, reaching the adult level in a variable period depending on the enzyme and the species involved [18,22], However, this rule has ex ceptions. Some enzymes have been reported to have an ontogenic development similar to that described in the present report.…”
Section: Resultsmentioning
confidence: 99%
“…Although most of the enzymes responsible for the metabolic degradation of drugs are present at birth, their activity usually is con siderably lower in neonates than in adults [ 18,19], A great number of drugs are eliminated from the body by metabolic pathways involv ing the CYP superfamily of enzymes, most of which are not expressed at the adult level throughout the early postnatal period [11,20,21], This fact, besides the reported enhanced perinatal sensitivity to some drugs, has created a cautious attitude towards drug use during the perinatal period, gestation and lac tation. As the animal grows up, the ability to metabolize xenobiotics becomes greater, reaching the adult level in a variable period depending on the enzyme and the species involved [18,22], However, this rule has ex ceptions.…”
Section: Resultsmentioning
confidence: 99%
“…The difference with the present experiment may be age-related because young pigs were used by Kokue et al (1994). Indeed, it has been shown that intestinal mucosa may be more permeable in young pigs than in adults to oral administration of polar antibiotics (Nouws 1992). It has been proposed that animals can absorb FA and utilize it after converting to a reduced form at the site of intestinal absorption and in the liver.…”
Section: Discussionmentioning
confidence: 65%
“…The high concentrations of roscovitine found in pup brain tissue indicate that roscovitine passes freely through the blood brain barrier (BBB). This difference in roscovitine kinetics might be due to the immaturity of the CYP450 enzymes responsible for roscovitine metabolism [149] or to the immaturity of the BBB. Roscovitine is metabolized mainly by the CYP3A4 and CYP2B6 enzymes in human [139].…”
Section: Age-dependent Kinetics and Pharmacodynamics Of Roscovitine Imentioning
confidence: 99%